PERTUMBUHAN BIBIT AREN (Arenga pinnata Merr) PADA MEDIA TANAH ULTISOL DIPERSEMAIAN - . Janting; Abdurrani Muin; . Burhanuddin (Universitas Tanjungpura, 2018)
Arenga pinnata Merr is a multipurpose trees species that has long been known to produce industrial materials. Based on the utilization of Arenga pinnata Merr is not only limited to the food alone but also used as a raw material for industrial and land conservation. Arenga pinnata Merr has prospect good to be developed in the tree crop plantations. Arenga pinnata Merr cultivation activities require good quality seeds. Currently Arenga pinnata Merr still growing naturally in the forest. Exploitation by the farmers during this time in the form of Arenga pinnata Merr exploitation of the forest without cultivation. There are concerns Arenga pinnata Merr that grows in nature will be destroyed. The purpose of this research to study the effect of a doses of organic fertilizer and dolomite lime on the growth of Arenga pinnata Merr in the nursery. The study used an experimental method with a completely randomized design factorial models. The study consisted of two factors: factors of organic fertilizer and lime dolomite with five repetitions with a number of plant samples as many as 100 plants. The measured parameters include length midrib, stem diameter and stem height were analyzed using SAS IX. The research proves that organic fertilizer dose of 300 g and 35 g dolomite lime can increase the growth of palm in the nursery. Keywords: Arenga pinnata Merr, fertilizer, lime, organic.